Frontiers in animal science - Frontiers Research Foundation (Frontiers Media S.A, 2020)
"Frontiers in Animal Science is an open access journal that publishes original, high-quality research in traditional and novel disciplines pertaining to the use of all animals (including insects and other invertebrates) for food production. Submissions are rigorously and transparently peer reviewed. Submissions with a focus on traditional aspects of livestock production, including nutrition, genetics, management and housing, are welcome. Advances in approaches and technologies concerning genomics, microbiome studies, precision livestock farming and automation that address the challenges mentioned above are encouraged. The journal also welcomes submissions on animal welfare science, the ethics of animal production, concept of animal sentience, consumer and stakeholder attitudes, environmental sustainability, governance and the role of animals in food security and health. Frontiers in Animal Science is a multidisciplinary Open Access platform dedicated to the dissemination of high-quality scientific articles in the field, bringing together experts from academia, industry, and policy spheres to inspire and promote cutting-edge research."--Publisher
Keywords: Agriculture : Periodicals; Animal culture : Periodicals; Livestock : Periodicals; Livestock; Poultry; Animal Nutritional Physiological Phenomena; Animal Welfare; Food Technology; Agriculture; Animal culture; Livestock